Dancing with Religion: Organized Atheism and Humanism in the Field of Religions in Denmark - Reeh, Niels (Numen, 2022)
The article firstly presents a modified version of a relational theoretical approach to the study of religions that can also be useful in the analysis of dynamic relations between religions and nonreligions. Nonreligious groups can be studied as relational collective groups that define themselves vis-à-vis other religious groups. Following this, the article suggests that scholars should take this relation between religions and nonreligions much further into consideration. Religious and nonreligious groups define themselves in a relation to what they perceive to be their most immediate competitors. Thus, the article posits that there is a social field of groups that relate and react to the other, and since we by convention know some of these groups as religions and nonreligions, we can study the set of interrelated groups as a social reality without the need of a definition. Instead of defining “religion” and “nonreligion,” the analysis can depart from the relation between the groups or the fact that both religions and nonreligions relate to and constitute themselves vis-à-vis other religions. In the last part, the article analyzes a piece of rare empirical evidence, namely, the founding event of a nonreligious group (i.e., the Danish Humanist Society). Here, the article shows how the Danish Humanist Society combined meaning and strategy in its relational struggle against its significant religious other, the Danish National Church.